Single Arterial Oxygen Tension Elevation Increases the Risk of Stage of Acute Disease Retinopathy of Prematurity - Pratiwi, Karina Satyani; Yulia, Dian Estu; Barliana, Julie Dewi; Sitorus, Rita Sita (International Journal of Retina, 2023)
Introduction: Numerous studies have shown inconclusive results regarding ideal parameter for oxygen supplementation to balance the risk of mortality and retinopathy of prematurity (ROP) development. The purpose of this study is to compare mean partial oxygen tension (PaO2) level in ROP. Methods: This retrospective study was performed on premature infants undergoing ROP screening at our neonatal intensive care unit during 2021. All infants born at our hospital at ≤ 30 weeks, birth weight (BW) ≤ 1500 grams, or high-risk infants with prolonged ventilation were included. ROP screening was performed at chronological age four to six weeks, were followed and managed according to the severity. ROP severity was categorized by International Classification of ROP 3rd edition (ICROP3). We reviewed the characteristics of each group and compared mean PaO2 level in day 1, day 5, and day 10 between incomplete vascularization (IV) group, stage of acute disease (SAD) group, and Aggressive ROP (A-ROP) group. Result: We investigated 124 eyes from 62 eligible PI. The incidence of IV, stage 1, stage 2, stage 3, and A-ROP were 58.9%, 2.4%, 7.3%, 23.4%, and 8.1%, respectively. Mean PaO2 level in day 5 was higher in SAD group compared to IV group (p=0.002). For each level increase in PaO2, there was 1.042 times higher odds of developing SAD (p=0.004). Multivariate logistic regression analysis showed consistent results, simultaneously, each week increase in GA was associated with lower risk of SAD development (p=0.018) and each level increase in PaO2 was associated with higher risk for SAD development (p=0.005). Conclusion: A single elevation in PaO2 during early life of PI increases the risk of developing stage of acute disease ROP, particularly in younger infants. Careful monitoring for PaO2 is mandatory to prevent development of ROP.